Turning Tool with Helical Cutting Edge for Optimizing the Machining Time Performance - Karol Vasilko; Zuzana Murčinková (Archives of Current Research International, 2016)
The paper presents turning with helical cutting edge employing the edge of twist drill and develops the special method of turning and its impact on the quality of machined surface. Finding the approach how to improve the surface quality and optimizing the machining time performance, the theoretical relation among the average maximum height of the machined surface profile Rz, the feed f and the radius of the tool tip rεis known. Increasing the feed f, the surface roughness Rz increases quadratically. On the other side, increasing rε, the surface roughness Rz decreasing hyperbolically. The limiting case is rε = ∞. The specification of such tool function is the cutting edge inclination angle λs. Another option is to use helical cutting edge. In such case, rε is curvature angle of helical edge. The experiments applied on different materials (dural and titanium alloys, brass) were performed to confirm the thesis of surface roughness quality improvement by use of helical cutting edge and moreover the significant increase in the productivity of turning were achieved regarding possibility to use several times larger feed rates.